Galvanic Couples in Ionic Liquid‐Based Electrolyte Systems for Lithium Metal Batteries—An Overlooked Cause of Galvanic Corrosion?. Issue 24 (7th May 2021) - Dohmann, Jan Frederik; Horsthemke, Fabian; Küpers, Verena; Bloch, Sophia; Preibisch, Yves; Kolesnikov, Aleksei; Kolek, Martin; Stan, Marian Cristian; Winter, Martin; Bieker, Peter
Abstract: The breakthroughs in rechargeable lithium metal‐anode‐based batteries is still challenged by safety and performance limitations. Ionic liquid (IL)‐based electrolytes are in consideration for increased safety but their moderate electrolyte performance and high costs still suppress their usefulness in Li metal‐batteries. In an effort to deepen the understanding of the limited performance, galvanic corrosion as an electrochemical degradation process is herein identified as a contributing factor toward battery cell deterioration. Four different ILs, based on bis(trifluoromethylsulfonyl)imide in combination with the quaternary ammonium cations N ‐butyl‐ N ‐methylpyrrolidinium, N ‐methyl‐ N ‐propyl‐pyrrolidinium, N ‐butyl‐ N ‐methylpiperidinium, and N ‐butyltrimethylammonium, respectively, are systematically investigated for such corrosive side reactions. The reaction pathways of this commonly neglected phenomenon are found to be both Hofmann‐type and reductive eliminations. Supported by headspace‐gas chromatography‐mass spectrometry, the evolving gaseous reaction products are characterized. With zero resistance ammetry and Li electrochemical dissolution and deposition experiments, the dependency of galvanic corrosion on the presence of the galvanically coupled materials is elucidated. Variation of the lithium bis(trifluoromethylsulfonyl)imide concentration in the electrolytes is shown to influence the extent of detectable degradation products. Based on these findings, the necessity for more sophisticated electrode designs and electrolyte formulations is emphasized. Abstract : In this work, the influence of galvanic corrosion is investigated for ionic liquid‐based electrolytes containing the bis(trifluoromethylsulfonyl)imide‐anion and four different quaternary ammonium cations. It is shown that lithium metal, while in contact to current collector materials, can cause redox‐reactions with the electrolyte. The extent of these side reactions is determined by the conductive salt content of the electrolyte.